Mimicking the Oxygen-Evolving Center in Photosynthesis - Chen, Yang; Xu, Boran; Yao, Ruoqing; Chen, Changhui; Zhang, Chunxi (Frontiers in Plant Science, 2022)
The oxygen-evolving center (OEC) in photosystem II (PSII) of oxygenic photosynthetic organisms is a unique heterometallic-oxide Mn4CaO5-cluster that catalyzes water splitting into electrons, protons, and molecular oxygen through a five-state cycle (Sn, n = 0 ~ 4). It serves as the blueprint for the developing of the man-made water-splitting catalysts to generate solar fuel in artificial photosynthesis. Understanding the structure-function relationship of this natural catalyst is a great challenge and a long-standing issue, which is severely restricted by the lack of precise chemical model for this heterometallic-oxide cluster. However, it is a great challenge for chemists to precisely mimic the OEC in laboratory. Recently, significant advances have been achieved and a series of artificial Mn4XO4-clusters (X = Ca/Y/Gd) have been reported, which closely mimic both the geometric structure and the electronic structure, as well as the redox property of the OEC. These new advances provide a structurally well-defined molecular platform to study the structure-function relationship of the OEC and shed new light on the design of efficient catalysts for the water-splitting reaction in artificial photosynthesis.